Lyssavirus surveillance in bats of southern China’s Guangxi Province - Lu, Zhuan-Ling (Virus Genes, 2012)
Although rabies virus is widely distributed in the world, and has been the subject of extensive investigations with the objective of its ultimate prevention, control, and management, there is much less knowledge of the characteristics, distribution, and infectivity of other lyssaviruses. Since bats are known animal vectors for all but one of the known lyssavirus genotypes, we have performed an extensive survey of bats in the Guangxi Province to provide information on lyssavirus distribution in southern China. The lyssavirus nucleoprotein gene was detected in brains of 2.86 % of 2,969 bats. Nucleotide sequence homologies among isolates were 86.9–99.6 %, but only 70.0–85.0 % for lyssaviruses in GenBank. These infected bats were detected from a wide area, essentially forming a band running from the south-west to the north-east of Guangxi, and it appears that infection by new lyssaviruses is widespread in this region.